1998
DOI: 10.1007/s002210050325
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of vestibular nerve irregular afferents to viewing distance-related changes in the vestibulo-ocular reflex

Abstract: The contribution of irregular vestibular afferents to viewing distance-related changes in the angular vestibulo-ocular reflex (AVOR) and combined angular and linear VOR (CVOR) was studied in squirrel monkeys trained to fixate earth-stationary targets that were near (10 cm) and distant (90-170 cm) from their eyes. Perilymphatic anodal galvanic currents were used to reversibly silence irregular vestibular afferents for periods of 4-5 s during the AVOR and CVOR evoked by 0.5- to 4-Hz sinusoidal rotations (6-20 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 18 publications
3
34
3
Order By: Relevance
“…In primates, these afferents have been shown to provide the major inputs to vestibulospinal pathways (Boyle et al, 1992). Irregular afferents also appear to be important for vergence-mediated changes in the vestibuloocular reflex (Chen-Huang and McCrea, 1998; Lasker et al, 2002; Migliaccio et al, 2008). Unless there are reciprocal temperature-dependent changes in the sensitivity to motion of central neurons, then responses of central processes and reflexes receiving irregular afferent inputs would be expected to decline as temperature falls.…”
Section: Discussionmentioning
confidence: 99%
“…In primates, these afferents have been shown to provide the major inputs to vestibulospinal pathways (Boyle et al, 1992). Irregular afferents also appear to be important for vergence-mediated changes in the vestibuloocular reflex (Chen-Huang and McCrea, 1998; Lasker et al, 2002; Migliaccio et al, 2008). Unless there are reciprocal temperature-dependent changes in the sensitivity to motion of central neurons, then responses of central processes and reflexes receiving irregular afferent inputs would be expected to decline as temperature falls.…”
Section: Discussionmentioning
confidence: 99%
“…As is almost always the case with ablation paradigms, such "negative" results are easier to interpret than are "positive" results. In particular, it cannot be concluded that a response diminished by the currents necessarily depends on irregular afferents (Chen-Huang et al 1997;Chen-Huang and McCrea 1998). This is because most responses involve polysynaptic pathways, which can carry regular, irregular, or mixed signals.…”
Section: Functional Ablation Of Irregular Afferentsmentioning
confidence: 91%
“…On the other hand, studies of the effects of the ablating currents on the linear VOR (LVOR) have produced inconsistent results. Chen-Huang and McCrea (1998) studied the eye movements produced during eccentric whole-body rotations, which include both AVOR and LVOR components. They reported that the ablating currents had only small effects and that these could be attributed to changes in the AVOR component.…”
Section: Functional Ablation Of Irregular Afferentsmentioning
confidence: 99%
“…Other vestibular nuclei neurons project to the ipsilateral or contralateral vestibular nuclei (Malinvaud et al, 2010), nucleus prepositus hypoglossi (McCrea and Baker, 1985; Kolkman et al, 2011), cerebellar flocculus (Highstein and Holstein, 2006), parabrachial nucleus (McCandless and Balaban, 2010), or to multiple brainstem nuclei regulating sympathetic outflow (Holstein et al, 2011). Still other vestibular nuclei neurons function as local circuit interneurons (Highstein and Holstein, 2006; Popratiloff and Peusner, 2011), or participate in the polysynaptic VOR pathways (Chen-Huang and McCrea, 1998). …”
Section: Structure/function Studies On the Vestibular Nuclear Complexmentioning
confidence: 99%